2022
DOI: 10.53765/20512201.29.11.080
|View full text |Cite
|
Sign up to set email alerts
|

'Contact' as a Manifestation of Sensorimotor Empathy: The Experience of Expert Écuyers in Interaction with Horses

Abstract: Chemero's concept of sensorimotor empathy offers a relevant introduction to the study of human/non-human relationships. This article proposes an empirical characterization of this phenomenon occurring in human–horse interactions through the notion of 'contact', which is a core concept in the technical tradition of the equestrian world. According to the assumptions of 4E cognition, we approach the notion of contact with a broader meaning than how it is usually defined, i.e.as the connection of the rider's hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The analysis of these interviews allowed for the identification of three categories of indicators: contact, balance, and hoofbeat. These categories of indicators were referenced from a prior study [5] and emerged from the verbalizations of the écuyers during thirty interviews. All interviews were selected because they delved into the notion of contact, which is central to equestrian technical culture.…”
Section: Background To the Development Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of these interviews allowed for the identification of three categories of indicators: contact, balance, and hoofbeat. These categories of indicators were referenced from a prior study [5] and emerged from the verbalizations of the écuyers during thirty interviews. All interviews were selected because they delved into the notion of contact, which is central to equestrian technical culture.…”
Section: Background To the Development Of Methodsmentioning
confidence: 99%
“…Unlike in the ridden condition, this in-hand condition is characterized by a substantial reduction in contact with the animal, limited to the mouth through the reins and to the touch points with the whip. The capacity to establish a "good" contact is built through a long appropriation by the écuyer of how the horse reacts and how to take this into account to act appropriately [5]. This progressive construction so as to "feel the horse" through the contact, especially in the preparation phase, is an important challenge in the écuyers' in-hand training.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the course-of-experience framework is that it offers a practical and empirical phenomenology potentially opening the documentation of mutual appropriation, intercorporeality and inter-enaction (Depraz, 2022). For example, it is possible to mention the study of Leblanc et al (2022), even if further empirical research must be done.…”
Section: Social | Individualmentioning
confidence: 99%
“…A joint analysis could clearly enrich the course-of-experience framework. The semiotic framework proposed by Iliopoulos (2019Iliopoulos ( , 2016, based on Peirce's triadic model, makes it possible to trace the nature, emergence and evolution of material signs and would be complementary to the documentation of 'practice as semiosis' within the course-of-experience framework, leading to a description that goes beyond human (Kohn, 2013;Leblanc et al, 2022).…”
Section: Materiality | Cognitionmentioning
confidence: 99%
“…This would be in line with the research focused on bodily awareness of athletes absorbed in a quest for performance activity, rebutting the association between expert skills and automaticity of movement execution (Gallagher, 2020; Montero, 2010). Secondly, we suggest that the process of appropriation of sports equipment that has behavior of its own, such as in sailing sports, may include the development of sensorimotor empathy (Chemero, 2016; Leblanc et al, 2022) together with a certain degree of incorporation. Indeed, the research we have presented in sailing has shown that sailors need to “understand” their craft’s movements and possibilities of movement through their own bodies.…”
mentioning
confidence: 99%